Developing sustainable careers for remote workers. Issue 2 (15th March 2022) - McDonald, Kimberly S.; Hite, Linda M.; O'Connor, Kimberly W.
ABSTRACT: As remote work becomes an option for many, ensuring career development in virtual workspaces will require innovative action from individuals and from HRD. Using the sustainable careers literature as a framework, this article explores how individuals can build viable and meaningful careers working remotely. The research indicates there are both advantages and challenges associated with virtual work. We address how Human Resource Development can help remote workers, maximize the advantages, and navigate the challenges to ensure the sustainability of their careers. In closing, we also offer implications for HRD research.